Posted by Shreya on Saturday, January 7, 2012 at 6:56pm.
do you mean
[ (4x+3)/(2x-1) ] - 2 = (6x+2)/(2x-1)
??????
If so please use parentheses so I can tell numerator from denominator.
If my guess is correct:
(4x+3) -2 (2x-1) = 6x+2
4x + 3 -4x + 2 = 6 x + 2
3 = 6 x
x = 1/2
sorry yes you are right but don't all 2x-1's cancel?
i think it supposed to be this
(4x+3)(-2) = (6x+2)
[ (4x+3)/(2x-1) ] - 2 = (6x+2)/(2x-1)
Multiply everything, all terms both sides including -2, by (2x-1)
[(4x+3)/(2x-1)](2x-1)-2(2x-1) = [(6x+2)/(2x-1) ] (2x-1)
You have to multiply that -2 by (2x-1) so the (2x-1) does not go away from the numerator when you clear it from the denominators.
so
(4x+3) -2 (2x-1) = 6x + 2
Perhaps your original line should read
[(4x+3)/(2x-1)](-2) = (6x+2)/(2x-1)
if so then
-2(4x+3) = 6x+2
-8x - 6 = 6x + 2
-14 x = 8
x = -4/7
and your answer would be right
thank you but in back of book it say no solution so i very confused.
If my solution of x = 1/2 is correct (and I think it is'
Then indeed the answer is NO SOLUTION
because
2x-1 = 0 if x = 1/2
division by 0
I did not notice that, should have.
thank you so much i not notice that either. thanks :)